2021
DOI: 10.1080/07317115.2021.1912239
|View full text |Cite
|
Sign up to set email alerts
|

Supported Web-Based Acceptance and Commitment Therapy for Older Family Caregivers (CareACT) Compared to Usual Care

Abstract: Objectives:The objective of the present study was to investigate whether an acceptance and commitment therapy (ACT)-based web-intervention (Group 1, CareACT), or a standardized rehabilitation in a rehabilitation center (Group 2) was effective in enhancing the psychological well-being of family caregivers aged 60 and over compared to support provided by voluntary caregiver associations (Group 3). Methods: Altogether, 149 family caregivers participated in this quasi-experimental study. Primary outcome measure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Previous studies have reported several advantages in using internet-delivered interventions with family carers of people with dementia. For instance, internet-based interventions facilitate access to support among family carers who are often unable to leave the care recipient unattended, as well as those limited by geographic and mobility constraints (Lappalainen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported several advantages in using internet-delivered interventions with family carers of people with dementia. For instance, internet-based interventions facilitate access to support among family carers who are often unable to leave the care recipient unattended, as well as those limited by geographic and mobility constraints (Lappalainen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this can lead to negative consequences for the care recipient, such as a reduction in their quality of life, increased use of healthcare services and institutionalization (Eska et al, 2013 ; Guterman et al, 2019 ; Martyr et al, 2018 ). Despite this, many carers are not able to access timely psychological support due to various barriers, such as reduced mobility, geographical location, lack of respite care, a shortage of skilled therapists leading to long waiting lists, and difficulties in prioritizing their own health needs (Green et al, 2012 ; Lappalainen et al, 2021 ; Tatangelo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that carers struggle to acknowledge their needs and to accept help in the ES of dementia (Boots et al, 2015). By exploring the retrospective views of experienced carers, this study not only identified the type of information and support that carers needed in the ES, but it also enabled to identify /telephone-delivered) that can facilitate access to those carers that cannot leave the care recipient unattended or that have geographical or mobility limitations (Lappalainen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of face‐to‐face delivered interventions, it is necessary to consider alternative modes of delivery (e.g. internet‐ /telephone‐delivered) that can facilitate access to those carers that cannot leave the care recipient unattended or that have geographical or mobility limitations (Lappalainen et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of RCTs of internet-delivered guided or non-guided self-help ACT demonstrated that internet-delivered self-help ACT can reduce depression and anxiety, although the majority of included studies targeted either general or student populations; studies that targeted family carers were not identified (Brown et al, 2016 ; Thompson et al, 2021 ). A more recent RCT explored the effectiveness of internet-delivered guided self-help ACT for informal carers aged 60 and over providing care to a spouse or child living with or without disease (Lappalainen et al, 2021 ). Twenty-six percent of participants were caring for a family member with memory-related problems and the findings demonstrated that internet-delivered self-help ACT guided by trained psychology and gerontology students was effective in reducing depression when compared to usual care, while no effects were found for anxiety.…”
Section: Introductionmentioning
confidence: 99%